PERENCANAAN KURIKULUM SEKOLAH DAN MADRASAH (Penelitian di SMAN 1 Singaparna dan MAN 2 Tasikmalaya) (Jurnal Tata Kelola Pendidikan, 2020)
This study aims to determine curriculum planning, supporting and inhibiting factors incurriculum planning in SMAN 1 Singaparna and MAN 2 Tasikmalaya. The results of thisstudy showed that curriculum planning at SMAN 1 Singaparna and MAN 2 Tasikmalayawas carried out by a curriculum development team consisting of principals or madrasas,deputy heads, teachers, administrative staff, committees, and education supervisors bytaking five basic frameworks, namely needs analysis, goal development, contentdevelopment, learning activities, and evaluation of curriculum planning. Curriculumplanning in SMAN 1 Singaparna is supported by the quality of the teachers andadministrative staff and the completeness of the facilities, but is hampered by some teacherswho still have a traditional-manual mindset, administrative complexity, and an incompleteunderstanding of 21st century education patterns. While the supporting factors in MAN 2Tasikmalaya are the quality of teachers and administrative staff, completeness of thefacilities, strict selection of students, and boarding school cooperation. However, thismadrasa faces resistances from the mindset of some teachers and time management forstudents who live in the boarding school.
Keywords: School; Madrasa; Curriculum Planning